2019
DOI: 10.1002/adfm.201808747
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Anomalous Hall Effect via Interfacial Scattering in Metal‐Organic Semiconductor Fex(C60)1−x Granular Films Near the Metal‐Insulator Transition

Abstract: Ferromagnetic metal-insulator granular films suffer from superparamagnetism, which causes a decrease in the values and temperature stabilities of the anomalous Hall effect (AHE). In this work, organic semiconductor (OSC) fullerene (C 60 ), instead of the traditional inorganic insulators, is used as the matrix and a series of Fe x (C 60 ) 1−x (x = 0.58-0.91) granular films are fabricated. By utilizing the strong metal/OSC interfacial hybridization, the temperature stability of both magnetization and AHE is sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It is well known that the ordinary Hall effect occurs in a conductor in the presence of a magnetic field and an electric current flowing perpendicular to it, and it is observed as an electric voltage induced in the direction that is perpendicular to both the electric current and magnetic field [70]. In FM materials, there is an additional contribution to the Hall voltage known as the anomalous Hall effect or the extraordinary Hall effect [66][67][68][69]71,72]. This contribution to the Hall voltage depends on the material magnetisation value, and in some materials, it can be much larger than the contribution of the ordinary Hall effect [66,68].…”
Section: Magneto-optical Kerr Effect and Anomalous Hall Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the ordinary Hall effect occurs in a conductor in the presence of a magnetic field and an electric current flowing perpendicular to it, and it is observed as an electric voltage induced in the direction that is perpendicular to both the electric current and magnetic field [70]. In FM materials, there is an additional contribution to the Hall voltage known as the anomalous Hall effect or the extraordinary Hall effect [66][67][68][69]71,72]. This contribution to the Hall voltage depends on the material magnetisation value, and in some materials, it can be much larger than the contribution of the ordinary Hall effect [66,68].…”
Section: Magneto-optical Kerr Effect and Anomalous Hall Effectmentioning
confidence: 99%
“…This contribution to the Hall voltage depends on the material magnetisation value, and in some materials, it can be much larger than the contribution of the ordinary Hall effect [66,68]. Since the anomalous Hall effect may originate from spindependent scattering of the charge carriers, one may expect that a change in the magnetic state and/or electrical conductivity of the sample under study would result in a change in Hall voltage [66][67][68][69]72].…”
Section: Magneto-optical Kerr Effect and Anomalous Hall Effectmentioning
confidence: 99%
“…These problems hamper the practical application of lithium metal anodes. [ 10 ] To address these issues, significant progress has been achieved in liquid electrolyte additives, [ 11–14 ] artificial solid electrolyte interphase (SEI), [ 15–18 ] polymer and solid electrolyte, [ 19–22 ] separator coating, [ 23–26 ] and 3D porous current collectors. [ 27–40 ] Among these strategies, the use of 3D porous current collectors is an efficient and convenient method to be capable of suppressing the growth of Li dendrites, because 3D conductive scaffolds with high specific surface area can provide sufficient surface areas and diffusion channels to balance the charge transport and transfer of lithium ions, diminish the local current density and reduce the nucleation overpotential.…”
Section: Introductionmentioning
confidence: 99%
“…C 60 in particular, as one type of fullerene, has attracted more attention than other organic materials because it is semiconducting and durable in mechanical and high-temperature processes [6][7][8][9][10]. Thus, the combination of C 60 and magnetic metals is expected to demonstrate tunable magnetic and electrical conducting properties, depending on the proximity effect of different alloy compositions and hetero-structures [2,[11][12][13][14][15][16][17][18]. Sakai et al reported high spin polarization at the Fe/C 60 interface in Fe-doped C 60 films [19].…”
Section: Introductionmentioning
confidence: 99%
“…A large spin-dependent transport length of approximately 110 nm was experimentally observed for the C 60 layer at room temperature [2]. At 2019 Zheng et al observed enhancement of the anomalous Hall effect in Fe x C 601−x granular films near the time of metalinsulator transition [11]. However, some questions remain unanswered regarding the magnetic properties of C 60 /3d transition-metal systems, such as whether C 60 can mediate magnetic exchange coupling between FM layers or nanoparticles?…”
Section: Introductionmentioning
confidence: 99%